PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI OLEH KEPUASAN KERJA KARYAWAN KOPERASI GRAHA CANTI SEMAWANG-SANUR - Sandiartha, I Wayan Bayu; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p13, 2020)
This study aimed to empirically examine the effect of job stress on job satisfaction, the effect of job stress on employee performance, the effect of job satisfaction on employee performance and the effect of job satisfaction mediating work stress on employee performance. Sampling in this study used a saturated or census sample technique, so the number of research samples was 42 employees. The population in this study were all permanent employees at the Graha Canti Semawang Cooperative in Sanur. Data were collected using a questionnaire and then analyzed using path analysis techniques (Path Analysis). The results showed that job stress has a negative and significant effect on job satisfaction and employee performance, job satisfaction has a positive and significant effect on employee performance, job satisfaction positively and significantly mediates the effect of work stress on employee performance. When work stress felt by employees is low, it can increase job satisfaction, so employee performance will increase. Keywords : Job Stress, Employee Performance, Job Satisfaction.